THEORETICAL BASES OF FORMATION AND DEVELOPMENT OF AGRICULTURAL ORGANIC PRODUCTION IN UKRAINE IN MODERN ECONOMIC CONDITIONS - Fedchyshyn, Dmytro (Economics of Agriculture, 2020)
The article discusses the current state of the global market for organic products and the main trends of organic production in Ukraine. The analysis of the main indicators of the leading countries in the production and sale of organic products is carried out. Based on a comparison of the indicators of the Ukrainian market for organic products with world leaders, it was concluded that the Ukrainian market for organic products needs: the formation and implementation of a national management model, improving legislation and the structure of certification organizations, drawing up a program of financial, information and marketing support for domestic producers.